1984
DOI: 10.1073/pnas.81.23.7579
|View full text |Cite
|
Sign up to set email alerts
|

Serological cross-reactivity between envelope gene products of type I and type II human T-cell leukemia virus.

Abstract: People exposed to type I human T-cell leukemia virus (HTLV-I) develop antibodies to an antigen at the surface of virus-infected cells, designated human T-cell leukemia virus membrane antigen (HTLV-MA). In an earlier study, we demonstrated that the major component of HTLV-MA is gp6l, a glycoprotein encoded by the HTLV env gene. In the current study, we found that human antibodies that react with HTLV-MA on cells infected with HTLV-I react equally well with HTLV-MA on C3-44/MO, a target cell infected with type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…These features make the 0.5a antibody an important reagent for studying the natural history and-biology of HTLV-I infections. It has been reported that viruses belonging to the HTLV-I family share some -common nucleotide sequences (24) and antigenic epitopes (1,25). However, the epitope that was recognized by 0.5a is apparently not one in common with the other members of the HTLV family.…”
Section: Discussionmentioning
confidence: 96%
“…These features make the 0.5a antibody an important reagent for studying the natural history and-biology of HTLV-I infections. It has been reported that viruses belonging to the HTLV-I family share some -common nucleotide sequences (24) and antigenic epitopes (1,25). However, the epitope that was recognized by 0.5a is apparently not one in common with the other members of the HTLV family.…”
Section: Discussionmentioning
confidence: 96%
“…They were both Italian heterosexual prostitutes, 28 and 58 years-old respectively, and had not travelled abroad. The most surprising finding of our investigation was the unexpectedly high number of HTLV-1-2 antibodies in syphilitic patients and in prostitutes who were seronegative for both HIV-1 and HIV-2, suggesting that HTLV-1-2 infection may occur independently of HIV-1 and HW-2, although considerable antigenic cross-reaction that HTLV-1-2 infection may occur independently of HIV-1 and HIV-2, although considerable antigenic cross-reaction between HTLV-1 and HTLV-2 (11,12,13,14) does take place. We cannot rule out the involvement of other viruses in the observed positivity.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that an additional program for detecting exposure to HTLV-1 have to be undertaken in order to stop the trasmission of this virus. We hope that a new test can be developed for the detection of specific antibodies, which, together with the use of type-specific probes against HTLV-1 and HTLV-2 (13,14), will help determine the real incidence of subjects with these different infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The viral envelope is generated as a polyprecursor protein (gp61) comprised of 488 amino acids which is cleaved into the surface domain (SU-gp46) and transmembrane domain (TMgp21) (20,21). SU binds to the cellular receptor(s), and then SU and TM undergo significant conformational remodeling, thereby exposing TM to facilitate membrane fusion and subsequent entry into the cell.…”
mentioning
confidence: 99%